Electronic commerce and music business development in Jamaica : a portal to the new economy? (UN New YorkUS, 2002)
Looks at music and electronic commerce and focuses on the potential impact of electronic commerce on the development of the music business in Jamaica. Examines electronic commerce and the Caribbean music industry in Canada.
Bibliography: p. 29-32